Wide Area Measurement Technology in Power Systems. (2016) - Sharma, R.B.; Dhole, G.M.
Abstract: Deregulation, competitive electricity market, expansion of transmission and distribution network, reliable electricity supply, increased applications of power electronics make the power system more complex. Therefore, many times power system has to operate closure to their maximum limits so as to use existing assets more efficiently. To operate under these constraints and still maintain high reliability is a very challenging task for power system generation, operation and planning requiring new intelligent system, technology and solutions. For decades, traditional supervisory control and data acquisition system (SCADA) measurements have been providing information on bus voltage, transmission line, generator, and transformer flows, transformer taps, breaker status as well as others system parameters. However, monitoring, operate and control of such large power system grid only steady state information may not be sufficient. Synchrophasor measurement technology (Wide area measurement technology) is a new term, which provides dynamic view of the grid. This paper introduces the role and advantages of using wide area measurement technology by answering three fundamental questions: what is wide area measurement technology; why is it needed and where does it best fit.